PP.37.10: DIFFERENCES BETWEEN OFFICE AND ABPM BLOOD PRESSURE VALUES IN PATIENTS WITH SLEEP APNEA-HYPOPNEA SYNDROME. (June 2015) - Vuckovic-Filipovic, J.; Milanov, S.; Davidovic, G.; Cekerevac, I.; Iric-Cupic, V.; Simic, I.; Ignjatovic, V.; Simovic, S.; Vuleta, M.
Abstract : Objective: More than 50% of patients with sleep apnea have hypertension and about 30% of hypertensives have sleep apnea as demonstrated in numerous studies. Aim was to determine the prevalence of hypertension in this specific group of patients and the difference between values measure in office and by using ABPM. Design and method: Research included 100 patients who underwent polysomnograpic examination in UCC Kragujevac. According to apnea-hypopnea index (AHI) all patients were divided into 4 equal groups, 25 patients in each group (AHI < 5; 5–15; 15–30 and > 30). Data for history of hypertension and antihypertensive treatment were collected anamnestically, and office blood pressure was measured baseline. All patients underwent single 24-h ambulatory BP monitoring. We calculated 24-h, daytime and nighttime blood pressure values separately for systolic and diastolic BP. All data were statistically analyzed in the SPSS for Windows. Results: Study population consisted of 69% of male and 31% of female patients with mean age of 55.05 ± 11.16 years. Prior hypertension was present in 76% of patients (x2 = 27.04; p = 0.000) in total group, with 68% on antihypertensive therapy (x2 = 12.96; p = 0.000). Among patients with diagnosed sleep apnea-hypopnea 62% had hypertension (x2 = 7.31; p = 0.007). The mean office SBP and DBP were both higher than guideline recomendations (140.39 mmHg SBP, 85.24 mmHg DBP). Mean values of BP were in mmHg: dSBP-134.13 ± 18.44; nSBP-125.67 ± 20.43; 24h-SBP-130.67 ± 18.28; dDBP-83.20 ± 12.16; nDBP-74.31 ± 11.94; 24h-DBP-79.69 ± 11.30. There was a significant difference between BP measured in office and by using ABPM for both, systolic and diastolic blood pressure (t-test; p = 0.000 and p = 0.001). Conclusions: Hypertension is highly prevalent in patients with sleep apnoea-hypopnea syndrome, with the majority of patients treated with antihypertensive therapy. There was a significant difference between blood pressure values measured in office, at the baseline, and by using ABPM, with higher values at the office.